CODE MIXING USED BY THE STUDENTS AND LECTURER IN SPEAKING CLASS AT ENGLISH EDUCATION STUDY PROGRAM - Abdulrahman, Yuli Yanti; Ismail, Ade; Firmansyah, Firmansyah (Cakrawala Bahasa, 2025)
This study aims to analyze the use of code-mixing by students and lecturers in speaking classes at the English Education Study Program of Khairun University. The focus of the research is to identify the types of code mix used and the factors that encourage code mix in the learning process. This study used a descriptive qualitative approach with data collection techniques through direct observation and in-depth interviews. The research subjects consisted of 45 first-semester students and one lecturer of “Speaking for Everyday Communication” course. The results of the observation research show that there are three types of code mix used, namely insertion, alternation, and congruent lexicalization, with insertion type as the most dominant form used by lecturers. In addition, of the 13 factors causing code-mixing, the interview results revealed three dominant factors that encourage the use of code-mixing by students and lecturers, namely (1) the use of more popular terms that are more easily understood by students, (2) the subject matter containing foreign terms or difficult concepts, and (3) the limitations of code usage in the use of English vocabulary which is the main obstacle in classroom communication. The findings reveal that the use of code-mixing is an important adaptation strategy for both parties in improving the understanding of teaching materials and facilitating communication in the learning process.